Model Technique on Grabstart Swimming Branch using Video Media for Deaf-Children - Anggri Dwi Nata; Achmad Sofyan Hanif; Abdul Sukur (University of Bengkulu, 2020)
The goal of this study was to produce a grabstart swimming training model using video media in deaf children and to determine the effectiveness, efficiency and attractiveness of the training model. This study uses adopted model from Research & Development by Borg and Gall. Subjects of the study were 40 deaf children consisting of 20 experimental groups and 20 control groups. The instrument used was a swimming-start skill test. The research steps were needs-analysis, expert evaluation, small and large group-test. The effectiveness test determines the level of deaf swimming-start skills of children after being given a grabstart swimming training model. Based on the average pretest-posttest value of the experimental group that were 49.92 to 56.18, there was an increase of 6.26 while the average value of the pretest-posttest control group was 50.02 to 52.20 with an increase of 2.18. Thus, it could be seen that training using the grabstart swimming training model using video media is more effective than the control group. We concluded that (1) the grabstart training model of swimming sports using video media can be developed and applied to deaf children, (2) the grabstart training model of swimming sport using video media is effective in improving the deaf children's swimming-start skills.